(untitled) (Journal of Global Accounting, 2025)
In line with accounting theory, earnings are taken into account as a measurement when assessing performance. This study examined the effect of earnings management on return on equity of listed non-financial firms in Nigeria. This study specifically seeks to ascertain the effect of discretionary accrual earning management and real earning management on return on equity of listed non-financial firms in Nigeria. The study adopted Ex post facto research design. The population of this study comprised of ninety-five (95). Purposive sampling technique was used to select seventy–four (74) listed non-financial firms as sample population. Data were obtained from secondary sources for a period of 13years covering 2011-2023. The study found amongst others that, discretionary accrual earning management and real earning management have no significant effect on return on equity of listed non-financial firms in Nigeria. Based on the findings of this study, it is recommended that since discretionary accrual earning management has no significant effect on return on equity, the study recommends that management should be encouraged to reduce their means of changing accounting estimates.